Incidence of functional training to potentiate strength in beginner swimmers of the Varadero club/Incidencia del entrenamiento funcional para potencializar la fuerza en nadadores semilleros del club Varadero - Christian Leonardo Maza Imbaquingo; Paulo Roberto Ñacato Delgado; María Lorena Sandoval Jaramillo (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
Functional training helps to enhance strength in certain muscle groups; in this way, the athlete improves body posture, gains muscle strength and endurance and, therefore, can increase indicators related to physical capacity and final performance. In this sense, the objective of the research was to apply a functional training program focused on the improvement of strength in beginner swimmers of the Varadero Club. The research is of descriptive-explanatory type of correlational order; a population of 17 swimmers (both genders; 14-16 years old) of the referred Club is diagnosed. A functional training adapted to the swimmer is applied on the basis of four physical indicators in two moments of applying said training. Significant differences are achieved in favor of the post- test in all the physical tests, both in the elbow flexion test (p=0.001) and in the abdominal test (p=0.001). In addition, the horizontal jump (p=0.005) and the vertical jump (p=0.001) are included. It is essential to potentiate the training of the physical capacity of strength in swimmers through a correct planning of functional training, given the strengthening of the muscles that intervene in the technical gesture. Four actions are recommended that influence the expansion of the study sample; emphasis is placed on the female gender; The results of the research are compared with other studies in other age ranges and a quasi-experimental type of research is carried out.